Karakteristik Peran Istri Nelayan dalam Meningkatkan Kesejahteraan Keluarga di Desa Saramake Kecamatan Wasile Selatan - Fanaria salim; Yetty; Musdar Muhammad; Muammil Sun’an; Jufri Jacob; Aswir Hadi (Jurnal Syntax Admiration, 2024)
This research aims to determine the characteristics and role of fishermen's wives in improving family welfare in Saramake Village, South Wasile District. This research is descriptive qualitative through interviews and observations. The research results show that the role of fishermen's wives in helping the family economy has increased family income from combined income. The fisherman's wife uses her income for daily needs. health care in hospital, The roles of fishermen's wives in Saramake Village include as wives, as housewives, and as educators for their children. The role of fishermen's wives in improving the family's economy has achieved prosperity, namely in terms of protecting the soul by fulfilling all daily needs and having a good and decent place to live. The reason for choosing to work at an anchovy processing place in Saramake Village is so that they can send their children to school, so that they can have the income earned by fishermen's wives as working women, to meet their family's daily needs.